Implementing Metal‐to‐Ligand Charge Transfer in Organic Semiconductor for Improved Visible‐Near‐Infrared Photocatalysis. Issue 32 (20th May 2016) - Li, Yanrui; Wang, Zhaowu; Xia, Tong; Ju, Huanxin; Zhang, Ke; Long, Ran; Xu, Qian; Wang, Chengming; Song, Li; Zhu, Junfa; Jiang, Jun; Xiong, Yujie
Abstract : The coordination of organic semiconductors with metal cations can induce metal‐to‐ligand charge transfer, which broadens light absorption to cover the visible–near‐infrared (vis–NIR) spectrum. As a proof‐of‐concept demonstration, the g‐C3 N4 ‐based complex exhibits dramatically enhanced photocatalytic H2 production with excellent durability under vis–NIR irradiation.